Emergency Traumatology at the N.V. Sklifosovsky Research Institute for Emergency Medicine: History and Modernity - A. M. Fain; V. B. Bondarev; A. Yu. Vaza; M. A. Malygina; I. Yu. Miguleva; K. V. Svetlov (Неотложная медицинская помощь)
The purpose of this work was to study the history of the development of traumatology-orthopedics at the N.V. Sklifosovsky Research Institute for Emergency Medicine.Traumatology as an independent discipline began to form at the N.V. Sklifosovsky Research Institute for Emergency Medicine during the reign of Professor S.S. Yudin (chief surgeon since 1928), who invited the famous Argentinean traumatologist-orthopedist Professor Lelio Zeno to work at the institute.In 1932, the trauma department of the N.V. Sklifosovsky Research Institute for Emergency Medicine was headed by Professor V.V. Gorinevskaya. She organized a 100-bed trauma clinic for the treatment of injuries to the head, spine, limbs, chest and abdominal cavity. She is rightfully considered one of the founders of trauma science in the USSR.With the development of traumatology and orthopedics as an independent specialty in 1961, two clinics were formed at the institute. The first trauma clinic was run by Dr. med. sciences professor I.I. Sokolov. The second clinic was headed by Dr. med. Sci. P.N. Petrov.In 1971, Dr. med. Professor, Honored Scientist of the Russian Federation, Academician of the Russian Academy of Medical and Technical Sciences of the Russian Federation V.P. Okhotsky was appointed the head of the traumatological service of the institute and the chief traumatologist of Moscow (from 1971 to 2001). With his active participation in Moscow, the reorganization of outpatient care was completed, work was widely launched on the medical aspects of the prevention of road traffic injuries and the introduction into practice of the most rational methods of diagnosis and treatment of patients with injuries of the musculoskeletal system. In the N.V. Sklifosovsky Research Institute for Emergency Medicine A.G. Suvalyan introduced the method of intramedullary osteosynthesis of long tubular bones (humerus, femur and tibia). Under the guidance of prof. V.P. Okhotsky the dissertation researches of A.G. Suvalyan, M.A. Suvalyan and S.S. Myakota were carried out. The expediency of early surgical intervention on the extremities in case of combined traumatic brain injury and multiple trauma of the extremities has also been proven, new functional methods of treatment of diaphyseal fractures of the shoulder, lower leg, spine and intra-articular injuries have been developed.In close scientific cooperation with scientists from other clinics of the institute, a comprehensive method of treating open injuries of the limbs has been developed (dissertation researches of I.F. Byalik, I.Yu. Klyukvin, O.P. Filippov, M.V. Zvezdina, R.S. Titov). Much scientific work has been carried out to improve the diagnosis and treatment of intra-articular injuries of the knee joint (dissertation researches by M.A. Malygina, O.P. Filippov, A.Yu. Vasa).From 2001 to 2016 the head of the department of emergency traumatology of the musculoskeletal system was a student of prof. V.P. Okhotsky – Dr. med. sciences, Professor, Academician of the Academy of Medical and Technical Sciences of the Russian Federation I.Yu. Klyukvin. Since 2016 the department is headed by Dr. med. sciences Alexey M. Fine.The scientific developments of the employees of the Department of Emergency Traumatology have a practical orientation. Every year, the department’s employees successfully perform more than 2500 surgical interventions using advanced low-traumatic techniques, making extensive use of the achievements of biotechnology.